Strategi Pengelolaan Dana Pihak Ketiga dalam Meningkatkan Likuiditas pada Bank Syariah Indonesia: Studi Kasus BSI KCP Probolinggo - Dinda Agustin; Muhammad Hifdil Islam; Maula Nasrifah (Economic Reviews Journal, 2024)
Banking is a company that operates in the service sector, the function of banking is to collect and distribute funds from the public. Fund collection plays a very important role for Bank Syariah Indonesia (BSI), because the funds collected will be distributed to the community in the form of financing and management of third party funds is an important aspect in managing bank liquidity, therefore the Bank has its own role. This research aims to find out how the Bank can utilize funding sources to increase its liquidity and to find out what strategies are implemented by the Bank. The method used is direct observation or interviews with the BSI KCP Probolinggo funding party. In analyzing the data, the author uses descriptive qualitative data analysis, which means the data is described systematically about the strategies carried out by PT. Indonesian Sharia Bank KCP Probolinggo. The research results reveal that the strategy used to increase and maintain TPF at Bank Syariah Indonesia is to seek large amounts of retail funds, offer competitive products, collaborate with business partners, cheap funds, not entrusted funds.